Measuring public sector capacity - Polidano, Charles (2000)
Explores the possibility of creating an index of public sector capacity which is 'policy neutral' and relies on information already available. Defines public sector capacity in terms of three elements: policy capacity, implementation authority and operational efficiency. Proposes a parallel index off ' enabling conditions' - environmental factors which lie beyond the control of the public sector, but which profoundly influence its capacity.